2018
DOI: 10.2147/ndt.s152747
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and acceptability of bibliotherapy for depression and anxiety disorders in children and adolescents: a meta-analysis of randomized clinical trials

Abstract: *These authors contributed equally to this workBackground: Depression and anxiety are the most common mental disorders in children and adolescents. Bibliotherapy is a treatment using written materials for mental health problems. Its main advantages are ease of use, low cost, low staffing demands, and greater privacy. Yet few meta-analyses have focused on the effect of bibliotherapy on depression and anxiety disorders in children and adolescents. Methods: We included randomized controlled trials comparing bibli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 57 publications
1
23
0
1
Order By: Relevance
“…[ 28 ] Hereditary and family factors play major role in causative factor for anxiety and depression among children and adolescents. [ 29 ] Many studies have shown that parental alcoholism has an effect on growing children. [ 12 13 14 15 16 17 18 19 20 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 28 ] Hereditary and family factors play major role in causative factor for anxiety and depression among children and adolescents. [ 29 ] Many studies have shown that parental alcoholism has an effect on growing children. [ 12 13 14 15 16 17 18 19 20 30 ]…”
Section: Introductionmentioning
confidence: 99%
“…The result of Yuan, et al, study suggests that bibliotherapy can reduce the depression felt of diabetes mellitus patients. 18 As the depression decreases, the self-efficacy of diabetes patient will increase.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conclude that "on the basis of currently available evidence, the effectiveness of these interventions for treating depressive disorders in children and adolescents cannot be established" (6). Findings from several large meta-analyses conducted since then have been consistent with this conclusion (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 93%